Analisa Penilaian Kondisi Jembatan Sarolangun Batang Tembesi Dengan Metode Bridge Manajemen System (BMS) - Pratama, Dicky Ardian; Handayani, Elvira; Dwiretnani, Annisaa; Suhendra, Suhendra (Jurnal Talenta Sipil, 2024)
Bridges are an important part of a road network system because they have a significant impact if the bridge collapses or if it does not function properly. A bridge is a structure that crosses a river or other traffic barrier, so the collapse of the bridge will reduce or hold back traffic, which as a result will disrupt the comfort of the public in traffic and disrupt economic relations. A bridge is a structure that crosses a river or other traffic barrier, which as a result disrupts people's comfort in traffic and disrupts economic relations (Bridge Inspection Guidelines 2012). Bridges are built so that pedestrians, vehicle or train drivers can cross these obstacles. However, it turns out that there are many types of bridges which of course vary both in terms of structure, strength and even construction costs. The main components of a bridge are the unity of the road embankment structure approaching the bridge, the sub-bridge structure and the bridge super-structure (BMS, 1993). The main objective of this research is to analyze the condition of the Sarolangun Batang Tembesi Bridge by observing it visually, assessing the technical condition of the bridge, and determining the priority order for bridge maintenance based on its condition value. However, the database results produced in this bridge management system are only limited to screening and ranking results in preparing bridge management programs (Directorate General of Highways, Bridge Management Systems, (1993), "IBMS General Procedure Guide", BMS, Department of Public Works of the Republic of Indonesia.